2013
DOI: 10.1186/1129-2377-14-48
|View full text |Cite
|
Sign up to set email alerts
|

Impact of continuing or quitting smoking on episodic cluster headache: a pilot survey

Abstract: BackgroundThe majority of patients suffering from cluster headache (CH) are smokers and it has been suggested that smoking may trigger the development of CH. The aim of this pilot survey was to describe: 1. the differences between current, former, and never smokers CH patients; 2. if smoking changed during an active cluster period; 3. if CH changed after quitting.MethodsAll outpatients with episodic CH according to the criteria of ICHD-II who were consecutively seen for the first time from October 2010 to Apri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 42 publications
4
54
1
2
Order By: Relevance
“…In a study of possible predictive factors in the evolution of episodic to chronic CH, Torelli et al concluded cigarette‐smoking rates and causality still cannot be established with certainty . In a recent paper, Ferrari et al state it is unlikely that there is a causal relationship between CH and smoking, as CH patients rarely improve after quitting smoking . For further discussion of this topic, please reference an excellent recent review of CH and substance issues including tobacco …”
Section: Clustermentioning
confidence: 99%
“…In a study of possible predictive factors in the evolution of episodic to chronic CH, Torelli et al concluded cigarette‐smoking rates and causality still cannot be established with certainty . In a recent paper, Ferrari et al state it is unlikely that there is a causal relationship between CH and smoking, as CH patients rarely improve after quitting smoking . For further discussion of this topic, please reference an excellent recent review of CH and substance issues including tobacco …”
Section: Clustermentioning
confidence: 99%
“…Cluster headache (CH) is unique among all the primary headache syndromes based on its association with cigarette smoking/tobacco exposure . If a CH patient has no personal history of tobacco use, then there is typically a history of secondary cigarette smoke exposure as a child from the patient's parents .…”
mentioning
confidence: 99%
“…Tobacco exposure is associated with a chronic state of CH . Some patients have smoked to manage pain attacks (eg, to distract from the pain) while others decreased their consumption to avoid exacerbation . In our case series, 5/7 patients reported daily use of tobacco (from 5 to 40 cigarettes a day), and cigarette consumption was identified as a trigger factor of CH by one of them.…”
Section: Discussionmentioning
confidence: 99%